2010
DOI: 10.2109/jcersj2.118.762
|View full text |Cite
|
Sign up to set email alerts
|

Hydrothermal synthesis and characterization of hydroxyapatite from octacalcium phosphate

Abstract: Hydroxyapatite (HA) particles synthesized by hydrothermal treatment of octacalcium phosphate (OCP) particles were characterized in detail and the reaction mechanism was discussed. The calcium-deficient HA particles were firstly formed and their compositions gradually closed to the stoichiometric composition with reaction progress. While their compositions closed to the stoichiometric composition, split of plate-shaped HA particles into smaller strips and subsequent crystal growth of HA particles were observed.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…In addition, we did not see any evidence for shift separation of the P5/P6 shift previously observed for OCPs. 22) This is consistent with the results of the XRD and FT-IR measurements. Figure 8 shows the Ca/PO 4 ratios obtained by FE-SEM/EDX for the materials formed with various acetic acid concentrations.…”
Section: Xrd Fourier Transform Infrared Spectroscopysupporting
confidence: 91%
“…In addition, we did not see any evidence for shift separation of the P5/P6 shift previously observed for OCPs. 22) This is consistent with the results of the XRD and FT-IR measurements. Figure 8 shows the Ca/PO 4 ratios obtained by FE-SEM/EDX for the materials formed with various acetic acid concentrations.…”
Section: Xrd Fourier Transform Infrared Spectroscopysupporting
confidence: 91%
“…A number of previous studies have described the formation of single crystal OCP rods, although the vast majority were formed under hydrothermal conditions, in the presence of organic additives. 52, 53 Large single crystal rods of HAP have also been formed under similar conditions, 54–58 and in some cases have been shown to form via similarly-sized OCP rods as an intermediary phase. 52, 53, 59, 60 Study of the transformation of OCP to HAP has suggested that this can occur by two mechanisms; the OCP dissolves and HAP then precipitates, or a direct solid-state transformation can occur, where hydrolysis of an OCP unit cell leads to a two unit cell thick layer of HAP.…”
Section: Resultsmentioning
confidence: 99%
“…52, 53 Large single crystal rods of HAP have also been formed under similar conditions, 54–58 and in some cases have been shown to form via similarly-sized OCP rods as an intermediary phase. 52, 53, 59, 60 Study of the transformation of OCP to HAP has suggested that this can occur by two mechanisms; the OCP dissolves and HAP then precipitates, or a direct solid-state transformation can occur, where hydrolysis of an OCP unit cell leads to a two unit cell thick layer of HAP. 16 In the latter case, the product HAP crystallites are pseudomorphs of the parent OCP, where the [001] axis of the parent OCP crystal is coincident with the [001] axis of the HAP product.…”
Section: Resultsmentioning
confidence: 99%
“…Microcrystalline samples of HA can also be prepared by solid-state reaction of other calcium phosphates (e.g., MCPM, DCPA, DCPD, OCP) with CaO, Ca(OH) 2 or CaCO 3 at temperatures above ~1,200°C in an atmosphere of equal volumes of water and nitrogen. HA can be prepared by hydrothermal synthesis 27 , 266 , 351 , 352 . A water-free synthesis can be performed in ethanol from Ca(OEt) 2 (Et = ethyl) and H 3 PO 4 353 , 354 .…”
Section: The Members Of the Calcium Orthophosphate Familymentioning
confidence: 99%